2018
DOI: 10.1249/mss.0000000000001456
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Response during Exercise and Mental Stress in Anabolic Steroid Users

Abstract: During muscle mechanoreflex activation (isometric exercise), AASU have normal MSNA and FBF responses, whereas during central command (mental stress) stimulation, AASU have exacerbated MSNA and blunted vasodilation. Therefore, mental stress seems to exacerbate neurovascular control throughout stress reaction situations in AASU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Blend 2: (371 mg) N-Acetyl-L-Tyrosine Caffeine (150 mg) Mucana pruitiens extract (15 mg) β-alanine (1600 mg) Arginine (1000 mg) 30 min prior to exercise. 30 min constant velocity treadmill running at 90% VT ↔ Fat oxidation [ 47 ] Hahn et al 2018 14 recreationally-active males Randomized, Double-blind, placebo-controlled, crossover design. L-Tyrosine (500 mg) Taurine (200 mg) Caffeine (120 mg) L-Carnitine (10 mg) Vitamin B6 (15 mg) Vitamin B12 (45 mcg) 20 min prior to exercise.…”
Section: Acute Effects Of Mips On Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Blend 2: (371 mg) N-Acetyl-L-Tyrosine Caffeine (150 mg) Mucana pruitiens extract (15 mg) β-alanine (1600 mg) Arginine (1000 mg) 30 min prior to exercise. 30 min constant velocity treadmill running at 90% VT ↔ Fat oxidation [ 47 ] Hahn et al 2018 14 recreationally-active males Randomized, Double-blind, placebo-controlled, crossover design. L-Tyrosine (500 mg) Taurine (200 mg) Caffeine (120 mg) L-Carnitine (10 mg) Vitamin B6 (15 mg) Vitamin B12 (45 mcg) 20 min prior to exercise.…”
Section: Acute Effects Of Mips On Performancementioning
confidence: 99%
“…Conversely, Jung et al [ 39 ] found that a MIPS with added synephrine increased REE ( d = 0.71, p < 0.05, large) and RER ( d = 1.14–1.66, p < 0.05, large) in recreationally-active male and female participants relative to placebo during a supine resting metabolic rate test. However, Erickson and colleagues [ 47 ] found no effect of acute MIPS consumption on fat oxidation in females during 30 min of treadmill running at 90% ventilatory threshold. Clearly, more investigations in a wider variety of populations are required before definite conclusions can be determined regarding any metabolic-related benefits.…”
Section: Acute Effects Of Mips On Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Anabolic androgenic steroids (AAS) have been associated with several cardiovascular injuries (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%